Isotype control of B cell signaling. - Silver, K; Cornall, R (2003)
The B cell receptor (BCR) consists of an antigen-binding membrane immunoglobulin (mIg) associated with the CD79alpha and CD79beta heterodimer. Naïve B cells express the IgM and IgD isotypes, which have very short cytoplasmic tails and therefore depend on CD79alpha and CD79beta for signal transduction. After antigenic stimulation, B cells undergo isotype switching to yield IgG, IgE, or IgA. Recent research suggests that the ability of the B cell coreceptor CD22 to regulate BCR signaling depends on the isotype of the mIg cytoplasmic tail. Cell lines that express a BCR with the cytoplasmic tail from IgG, the isotype found in memory B cells, are not subject to CD22 regulation, whereas cell lines that express BCRs with IgM cytoplasmic tails are subject to CD22 regulation. Moreover, stimulation through BCRs containing an IgG cytoplasmic tail causes increased numbers of antigen-specific clones to accumulate. These observations are a valuable step toward understanding the difference in B cell signaling between na ve and memory cells. Here, we discuss the implications of these findings for CD22 regulation and signaling through the mIgG-containing BCR.